Tourism Development and Socio-Economics Enhancement of Communities in Sarawak - Komathi, Wasudawan (Universiti Malaysia Sarawak (UNIMAS), 2018)
Pro-poor tourism is recognised as an effective socio-economic tool in Sarawak, Malaysia. Therefore, this study examines the impact of tourism development (local economy development, tourism entrepreneurial activity, tourism employment generation, capacity building, stakeholders' support, community participation, infrastructure development, rural culture, cultural attraction, rural environment and environmental conservation) on poverty alleviation. The study also measures the moderator effect oftourism resources (i.e., cultural, nature, wildlife, rural and physical) between tourism development and poverty alleviation. A quantitative primary data from individuals from tourism channels is generated. The SmartPLS 3.0 (M3) and Statistical Package for Social Sciences (SPSS) version 22.0 are used to analyse the primary data from 520 respondents. A total of 22 hypotheses are tested in the study, however 10 of the hypotheses show positive results. Based on the effect size, poverty alleviation can be achieved with local economic development and stakeholders' support. In addition, an equal distribution oftourism resources among the stakeholders, locally managed tourism businesses, increasing in capacity building and preserving nature and culture could balance the socio-economic livelihood. Future research in Sri Aman, Sibu, Limbang, Kapit and Mukah is highly recommended. These five divisions in Sarawak have potential for sustainable tourism development and pro-poor tourism.